PC.115 Audit of Neonatal Enteral Nutrition in Northern Ireland. (9th June 2014) - Courtney, J; Gupta, C; Mayes, C; Craig, S
Abstract : The practices and support for delivery of Neonatal Enteral Nutrition (EN) in Northern Ireland were audited against standards derived from the NICE Quality Standards for Specialist Neonatal Care. Method: The records of the first 40 babies consecutively admitted to 5 neonatal units in Northern Ireland after 1st April 2012 were audited (~10% of all NI admissions). Results: All units have breastfeeding policies and 80% EN progression guidelines Infant characteristics were gestation median (range) 34 (24–41) weeks; birthweight median (range) 2.24 (0.6–4.97) kg. EN commencement median (range) was 1 (0–74) days. Full EN was reached median (range) 4 (0–21) days. Initial milk used was; 48% expressed breast milk (EBM), 35% formula, 14% donor EBM (DEBM) and 3% never received EN. 63% of all babies received some EBM; 27% received DEBM. Milk at full EN was; 36% formula, 30% EBM, 14% EBM + formula, 9% DEBM, 7% none. On discharge 55% were on formula, 28% EBM. Median (range) of corrected age at discharge was 37 (28–44) weeks with weight median (range) 2.47 (0.8–4.97) kg. Patient outcomes; 75% home, 19% transferred, 4% postnatal ward, 2% died. Conclusion: Despite increasing evidence of the benefits of maternal breast milk for preterm infants, rates of EBM use fell from 48% on initiation to 28% at discharge. Only 63% of neonatal admissions in Northern Ireland ever received maternal breastmilk. A Quality Improvement Initiative should commence supporting mothers breastfeeding and expressing milk for their infants.